(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the early growth performance of naked neck, normal and frizzle-feathered Nigerian native chickens, under intensive system. 150 chicks, comprising 50 chicks from each genotype, were used in a 3 X 2 factorial arrangement in a Completely Randomized Design (CRD), with genotype and sex as factors of interest. Data were collected on hatch weight, weekly body weights, and total weight gain. The result showed no significant genotype effect (P>0.05) on hatch weight and body weight at week one. From week 3 to week 8, naked neck and frizzle-feathered chicks had comparable body weights, which differed significantly (P<0.01) from that of the normal feathered chicks. Naked neck genotype had significantly (P<0.05) higher total weight gain than frizzle and normal-feathered Nigerian native chickens, which had comparable total weight gain. Sex had highly significant (p<0.001) influence on hatch weight, body weight from week 1 to week 8, and total weight gain. Genotype X sex interaction had significant (p<0.05) effect on hatch weight, but no significant (p>0.05) effects on body weight of Nigerian indigenous chickens from week 1 to week 8. Naked neck and frizzle-feathered males had comparable total weight gain, which were higher than that of normal feathered males and all females irrespective of genotype. Naked neck females had significantly (P<0.01) higher total weight gain than normal and frizzle-feathered females, which had comparable total weight gain. It could be concluded that the naked neck genotype performed better than the frizzle and normal-feathered Nigerian native chickens under intensive system of management.